2020
DOI: 10.7554/elife.53360
|View full text |Cite
|
Sign up to set email alerts
|

Dual histone methyl reader ZCWPW1 facilitates repair of meiotic double strand breaks in male mice

Abstract: Meiotic crossovers result from homology-directed repair of DNA double-strand breaks (DSBs). Unlike yeast and plants, where DSBs are generated near gene promoters, in many vertebrates DSBs are enriched at hotspots determined by the DNA binding activity of the rapidly evolving zinc finger array of PRDM9 (PR domain zinc finger protein 9). PRDM9 subsequently catalyzes tri-methylation of lysine 4 and lysine 36 of Histone H3 in nearby nucleosomes. Here, we identify the dual histone methylation reader ZCWPW1, which i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(77 citation statements)
references
References 86 publications
5
71
1
Order By: Relevance
“…Consistent with this idea, ZCWPW1 binding is positively associated with levels of both H3K4me3 and H3K36me3 marks ( Figure 6—figure supplements 1 and 2 , tested separately, not necessarily ‘dual’ marks coincident within an individual cell, although locations of these marks in meiotic cells are rarely coincident except at hotspots [ Powers et al, 2016 ]). While we cannot rule out a direct interaction between ZCWPW1 and PRDM9, others have shown that dual modified peptides have a greater affinity to ZCWPW1 than peptides carrying the single modifications, supporting that the marks themselves are responsible for ZCWPW1’s recruitment ( Mahgoub et al, 2020 ). We examined transcription start sites, which possess H3K4me3 at high levels, but lack H3K36me3, observing some ZCWPW1 signal at these sites, but with a uniformly lower mean ZCWPW1 enrichment compared to those with evidence of PRDM9 binding (and hence both histone marks) ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Consistent with this idea, ZCWPW1 binding is positively associated with levels of both H3K4me3 and H3K36me3 marks ( Figure 6—figure supplements 1 and 2 , tested separately, not necessarily ‘dual’ marks coincident within an individual cell, although locations of these marks in meiotic cells are rarely coincident except at hotspots [ Powers et al, 2016 ]). While we cannot rule out a direct interaction between ZCWPW1 and PRDM9, others have shown that dual modified peptides have a greater affinity to ZCWPW1 than peptides carrying the single modifications, supporting that the marks themselves are responsible for ZCWPW1’s recruitment ( Mahgoub et al, 2020 ). We examined transcription start sites, which possess H3K4me3 at high levels, but lack H3K36me3, observing some ZCWPW1 signal at these sites, but with a uniformly lower mean ZCWPW1 enrichment compared to those with evidence of PRDM9 binding (and hence both histone marks) ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 79%
“…Like DMC1, RPA2 levels were also significantly elevated in the Zcwpw1 −/− mouse from zygotene onwards ( Figure 4—figure supplement 2 ). In Zcwpw1 −/− males, like in the Prdm9 −/− mutant, DSBs form and recruit RPA2, RAD51 and DMC1 in similar numbers ( Huang et al, 2020 ; Li et al, 2019a ; Mahgoub et al, 2020 ), but fail to repair efficiently, accompanied by asynapsis and meiotic arrest at pseudo-pachytene. Indeed, we observe late unrepaired DMC1 foci mainly on HORMAD2-positive asynapsed chromosomes ( Figure 4—figure supplement 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…ZCWPW1 is a factor that participates in repairing PRDM9-induced DSBs during meiosis. This study, made possible with NGS and END-seq, demonstrated the tight regulation that is ensued due to the collaboration between ZCWPW1 and PRDM9 [99].…”
Section: Cells 2020 9 X For Peer Review 7 Of 19mentioning
confidence: 75%
“…As no evidence of HELLS/TET interaction in meiotic cells is available, a PRDM9-dependent chromatin modification might be implicated in recruiting the putative TET activity. ZCWPW1, a reader of H3K4me3 and H3K36me3 that is required for efficient DSB repair ( Huang et al, 2020 ; Mahgoub et al, 2020 ; Wells et al, 2019 ), might be directly or indirectly involved in this recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these histone modifications may play a role in DSB repair. Indeed, ZCWPW1, a protein reader of H3K4me3 and H3K36me3, is required for efficient DSB repair ( Huang et al, 2020 ; Li et al, 2019 ; Mahgoub et al, 2020 ; Wells et al, 2019 ). Whatever their exact role, the presence of both histone modifications leads to a unique chromatin landscape at PRDM9 sites that is not present at promoters, where H3K36me3 is depleted ( Grey et al, 2017 ; Lam et al, 2019 ; Powers et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%